VD_FINDINFO Jug / 2016 / 3 vom 29. April 2015 - VD Tribunal cantonal (2015)
CONSTATATION DES FAITS, FIXATION DE LA PEINE, SURSIS À L'EXÉCUTION DE LA PEINE, INDEMNITÉ ÉQUITABLE, CONTRAINTEDROIT PÉNAL | 33 CP, 42 CP, 47 CP, 429 CPP (CH), 433 al. 1 CPP(CH)